Synthesis and characterisation of new antimalarial fluorinated triazolopyrazine compounds - Lum, Kah Yean; White, Jonathan M.; Johnson, Daniel J. G.; Avery, Vicky M.; Davis, Rohan A. (Beilstein Journal of Organic Chemistry, 2023)
Nine new fluorinated analogues were synthesised by late-stage functionalisation using Diversinate™ chemistry on the Open Source Malaria (OSM) triazolopyrazine scaffold (Series 4). The structures of all analogues were fully characterised by NMR, UV and MS data analysis; three triazolopyrazines were confirmed by X-ray crystal structure analysis. The inhibitory activity of all compounds against the growth of the malaria parasite Plasmodium falciparum (3D7 and Dd2 strains) and the cytotoxicity against a human embryonic kidney (HEK293) cell line were tested. Some of the compounds demonstrated moderate antimalarial activity with IC50 values ranging from 0.2 to >80 µM; none of the compounds displayed any cytotoxicity against HEK293 cells at 80 µM. Antimalarial activity was significantly reduced when C-8 of the triazolopyrazine scaffold was substituted with CF3 and CF2H moieties, whereas incorporation of a CF2Me group at the same position completely abolished antiplasmodial effects.
Keywords: antimalarial; characterisation; DiversinateTM; fluorine; triazolopyrazine; scaffold; Open Source Malaria